Manda nudes, bebê: relações de gênero e sexualidades na prática do sexting entre adolescentes no ambiente escolar - Smyl, Elaine Beatriz de Oliveira (2020)
The term sexting is a blend of two English words, sex and texting. Sexting is the sociocultural practice of sharing, receiving, and exchanging written messages, emojis, photos, and videos of an erotic/sensual/sexual nature, primarily through the cell phone. This paper will discuss sexting as a gendered technology that acts to produce subjectivities, contributing to the creation and expression of masculinities and femininities among adolescents at a public school in Curitiba, Brazil. The data include narratives collected from a group of students between 15 and 18 years of age. As the environment of this study, the school often serves as the location where the materials related to sexting are produced, passed on, viewed, and commented on. The extreme consequences of this practice are also perceived within the school, particularly in terms of non-consensual sharing of material, which leads to cases of bullying, violence, and other aggressions. The students’ narratives indicate that sexting intersects with gender signs, sexuality, body type and age group that can reinforce hegemonic norms. However, this practice also makes it possible to produce new representations that challenge the markers of conventional masculinities and femininities.